Older men and older women remand prisoners: mental illness, physical illness, offending patterns and needs. (May 2015) - Davoren, Mary; Fitzpatrick, Mary; Caddow, Fintan; Caddow, Martin; O'Neill, Conor; O'Neill, Helen; Kennedy, Harry G.
ABSTRACT Background: Older prisoners are the fastest growing group of prisoners in most countries. They have high rates of physical and psychiatric co-morbidity, compared to community dwelling older persons and also compared with other prisoner groups. Very high rates of mental illness have been found in remand (pre-trial) prisoners when compared with other prisoner groups; however to date there have been no studies examining older male and female remand prisoners. Methods: A retrospective chart review was conducted of all remands, to a male and a female prison, over a six and half-year period. Demographic data were collected pertaining to psychiatric and medical diagnoses and seriousness of offending. Results: We found rising numbers of older prisoners amongst male remand prisoners. Older remand prisoners had very high rates of affective disorder and alcohol misuse. They had rates of psychotic illnesses and deliberate self-harm comparable to younger remand prisoners. High rates of vulnerability were found among older prisoners and older prisoners had a greater need for general medical and psychiatric services than younger prisoners. We also found comparable offending patterns with younger prisoners and high rates of sexual offending among the older male prisoner group. Conclusions: Given the ageing population of many countries it is likely the numbers of older prisoners will continue to grow and given their high levels of both physical and psychiatric illness this will have implications for future service delivery.